Workspace as a factor of job satisfaction in the banking and ICT industries in Macedonia - Tomovska Misoska, Ana; Stefanovska-Petkovska, Miodraga; Ralev, Misko; Krliu-Handjiski, Venera (Serbian Journal of Management, 2014)
Job satisfaction has always been an interesting topic among the business community. One important aspect that gains more and more prominence is the relationship between physical aspects of the workspace and experienced level of job satisfaction. Although there is numerous research exploiting the link between workspace and job satisfaction in European and worldwide companies there is a lack of such research in the Republic of Macedonia and the Balkan region. Therefore the objective of this study is to investigate the relation between physical workspace environment, workspace satisfaction and employees’ job satisfaction in the banking and ICT sector in the Republic of Macedonia. The study is quantitative using a questionnaire as a main research instrument implemented among 250 employees. The analysis is concentrated on uncovering the impact of various aspects of the workspace design and personalization of the workspace on workplace satisfaction and through that on job satisfaction. The results confirm that workspace satisfaction and job satisfaction depend on various elements of workspace design. Therefore significant attention should be paid to employees’ perception of the workspace and the design of various aspects of the workspaces.